Automatic Crawling of Information to Address the Disaster Information Management - Priyadharshini,, B Angeline; IlancheziaPandian, G. (IJRDO -Journal of Computer Science Engineering, 2015)
In recent years, the efficiency of sharing and managinginformation plays an important role in business recoveryefforts after disaster event. The first issue is that reconstructingor creating information flow becomes intractable in domains.The improvement of Crisis Management and DisasterRecovery techniques are national priorities in the wake ofman-made and nature inflicted. Users are eager to findvaluable information to help them understand the currentdisaster situation and recovery status.Data mining andinformation retrieval techniques help impacted communitiesbetter understand the current disaster situation and how thecommunity is recovering. Report characterization techniquesgenerate brief reviews from a large collection of reports atdifferent granularity. Probabilistic models with Locationspecific resource identification algorithm support dynamicallygenerating query forms and information dashboard based onuser feedback; and community generation and userrecommendation techniques are adapted to help users identifypotential contacts for report sharing and communityorganization.